Influence of antidepressant therapy on sick leave in primary care: ADAS, a comparative observational study. Issue 1 (January 2019) - Skoglund, Ingmarie; Björkelund, Cecilia; Svenningsson, Irene; Petersson, Eva-Lisa; Augustsson, Pia; Nejati, Shabnam; Ariai, Nashmil; Hange, Dominique
Abstract: Background: Compared to other European countries, Sweden's yearly sick leave expenditures are moderate. Common mental disorders (CMD) are important causes of sick leave, affecting 10–15% of the adult population. A Swedish register based study indicates that antidepressant therapy for patients on long-term sick leave for CMD leads to longer sick leave and higher frequency of non-time-limited sickness compensation as compared to psychotherapy, work oriented rehabilitation, and other therapies. Aim: To verify if patients on antidepressant therapy and on long-term sick leave for depression, anxiety and stress-related mental disorders have a longer sick leave than patients treated with other therapies. Method: Prospective, observational study at 28 primary health care centers in the Region Västra Götaland, Sweden, including 192 patients on sick leave for CMD. Outcome measures were gross and net sick leave days. Interpretation: There were no significant differences in sick leave days (gross or net) due to CMD when comparing the patients treated and not treated with antidepressants during the 12 month observation period. The groups differed at baseline only concerning frequency of exhaustion disorder, with a higher frequency of exhaustion disorder in the group without antidepressants. Analysis of other possible factors associated with shorter or longer sick leave only showed associations with the patient's own perception of possibility of returning to work in near and distant future. An important factor associated with longer sick leave was the patient's own perception of possibility of return to present workplace. As CMD are important causes of sick leave and sick leave costs, this factor should be highlighted in future research on the rehabilitation process.